Iliac intramedullary stabilization for Type IIIA fragility fractures of the pelvis - Shingo Okazaki (Nature Portfolio, 2020)
Abstract There have been few reports on fixation of Rommens classification Type IIIA fragility fractures of the pelvis (FFPs). Here, we present our less invasive surgical technique, called iliac intramedullary stabilization (ILIS), for the internal fixation of Type IIIA FFPs. The technique involves a closed reduction, termed the femur internal rotation reduction method (FIRM), whereby the fracture fragments are repositioned using lateral rotators by internally rotating the femur while the patient is in the prone position. Two iliac screws are inserted on the ilium bilaterally via the supra-acetabular bone canal during FIRM and connected with two transverse rods and two cross connectors. We refer to this internal fixation procedure as ILIS. We retrospectively recruited patients with Type IIIA fractures, treated using this procedure, at our institute between October 2017 and October 2019. We evaluated operative and post-operative outcomes. We enrolled 10 patients (9 women and 1 man; mean age, 85.2 years) who were followed up for over 6 months. All patients suffered FFPs after falling from a standing position. The mean operative time was 145.1 (range, 94–217) minutes, and the mean blood loss was 258.5 (range, 100–684) ml. All patients were allowed full weight bearing from post-operative day 1. All patients achieved bone union and regained their pre-injury walking ability at 6 months after surgery without evident secondary displacement. In conclusion, our ILIS technique allows less invasive internal fixation of Type IIIA FFPs with adequate stability for full weight bearing from post-operative day 1.